Preparation method of negative ion antibacterial modified colored DTY (Draw Textured Yarn) low stretch yarn
By using bamboo charcoal particles and silicon oxygen wrapping layer in polyester low-elastic wire to form a negative ion release system and porous silicon oxygen filler, the problem of poor antibacterial performance and durability of polyester low-elastic wire is solved, and the antibacterial stability and mechanical properties are improved, satisfying the satisfaction of Market demand.
Patent Information
- Application Number
- CN202411649614.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing polyester low-elastic wire has poor antibacterial properties and is prone to damage, and has insufficient antibacterial stability.
采用竹炭颗粒形成负离子释放体系,并通过硅氧包裹层在竹炭颗粒表面形成介孔结构和阻隔性,结合多孔硅氧填料以提高抗菌性和机械性能。
It significantly improves the antibacterial stability and mechanical properties of polyester low-elastic wire, ensures the durability of antibacterial effects and the color transferability of masterbatch, and meets the market's high-quality demand for polyester low-elastic wire.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical fibers, and in particular relates to a method for preparing negative ion antibacterial modified colored DTY low-elastic yarn. Background Art
[0002] Polyester low-elastic yarn, also known as DTY, is a type of textured yarn of polyester chemical fiber. It is made of polyester chips (PET) through high-speed spinning, drawing and false twisting. It has the advantages of polyester material's breaking strength, good resilience, heat resistance, light resistance, and corrosion resistance, and is widely used in clothing fabrics, bedding, and decorative products.
[0003] As people's living standards improve, the quality requirements for fabrics are getting higher and higher. Among them, antibacterial property has gradually become a common property of polyester low-stretch yarn. The antibacterial property of existing polyester low-stretch yarn is obtained by coating the surface of the polyester low-stretch yarn with an antibacterial agent after the polyester low-stretch yarn is spun. However, the antibacterial property only exists on the surface of the polyester low-stretch yarn, has poor durability, and is very easy to be damaged. Summary of the invention
[0004] In view of the problems in the prior art, the present invention provides a method for preparing negative ion antibacterial modified colored DTY low-elastic yarn, which solves the problem of poor antibacterial stability of the existing polyester low-elastic yarn. Bamboo charcoal particles are used to form a negative ion release system, and the surface of the bamboo charcoal particles is used to form a silicon-oxygen mesoporous release channel and barrier property, thereby ensuring the antibacterial and stability of the polyester low-elastic yarn.
[0005] In order to achieve the above technical objectives, the technical solution of the present invention is: A method for preparing negative ion antibacterial modified colored DTY low-elastic yarn comprises the following steps: Step 1, pre-crystallizing polyethylene terephthalate slices at high temperature, then drying, and ball milling to obtain pre-crystallized polyethylene terephthalate fine powder, wherein the temperature of the high-temperature pre-crystallization is 170-175° C., the temperature of the drying treatment is 180-185° C., and the time is 5-7 hours; the pressure of the ball milling treatment is 0.4-0.6 MPa, and the temperature is 5-10° C.; in this step, the polyethylene terephthalate slices are converted into spherical crystals by means of high-temperature pre-crystallization, and a fine powder structure is formed after ball milling; Step 2, adding the modified anion fine powder, the masterbatch and the reinforcing filler to the pre-crystallized polyethylene terephthalate fine powder and mixing them evenly, and then adding them to a twin-screw extruder for melt extrusion to obtain a mixed melt, wherein the mass ratio of the mixed melt is: 180-200 parts of pre-crystallized polyethylene terephthalate fine powder, 8-10 parts of modified anion fine powder, 3-5 parts of masterbatch, and 5-10 parts of reinforcing filler; the modified anion fine powder adopts modified bamboo charcoal particles, and the masterbatch adopts magenta masterbatch , one or more of cyan masterbatch and yellow masterbatch, the reinforcing filler is a porous silica filler; the temperature of the melt extrusion is 280-290°C, and the pressure is 7-8MPa; this step uses modified anion fine powder, masterbatch, reinforcing filler and pre-crystallized polyethylene terephthalate fine powder to form a blend to achieve full mixing, and in the process of melt extrusion, the modified anion fine powder, masterbatch and reinforcing filler are promoted to be fully dispersed in the pre-crystallized polyethylene terephthalate fine powder to obtain a mixed melt; Step 3, adding the mixed melt into the spinning box, and cooling it evenly into POY- with annular blowing, and obtaining the negative ion antibacterial modified colored DTY low-elastic yarn through texturing treatment, the spinning temperature is 285-295°C, the temperature of the annular blowing is 22-25°C, the wind speed is 0.5-0.7m / s, and the humidity is 65-85%; the texturing treatment is to sequentially pass the spinning through a pre-network nozzle, a yarn guide, a roller, a false twister, a second roller, a final network, a third roller and a winding roller to obtain a polyester low-elastic yarn.
[0006] Among them, the modified bamboo charcoal particles are made of silicone-wrapped bamboo charcoal particles, and there are gaps between the bamboo charcoal particles and the silicone-wrapped layer. The bamboo charcoal particles have a loose and porous structure, which not only has good super-strong adsorption capacity, but also can produce negative ions, which have the effect of mildew prevention and antibacterial. However, the bamboo charcoal particles also have the problem of moisture absorption and humidity regulation, which not only affects the moisture absorption of the polyester low-elastic yarn, but also affects the antibacterial effect. To address this problem, silicone-wrapped bamboo charcoal particles use a silicone wrapping layer to coat the bamboo charcoal particles to achieve a good barrier effect without affecting the release of negative ions.
[0007] The preparation method of silicon-oxygen-wrapped bamboo charcoal particles comprises the following steps: a1, wet-grinding bamboo charcoal particles for 2-4 hours, and obtaining bamboo charcoal fine powder after evaporation; the wet-grinding uses ether as solvent, and the mass ratio of bamboo charcoal particles to ether is 3-5:1, and the grinding pressure is 0.3-0.5MPa; the evaporation temperature is 40-50°C; this step uses wet-grinding to refine bamboo charcoal particles, and uses ether as a buffer, which can quickly absorb heat and reduce the influence of friction temperature.
[0008] a2, putting ethyl cellulose into ether to form a dissolving solution, and putting bamboo charcoal fine powder into it, after ultrasonic treatment for 1-2h, filtering and drying to obtain coated bamboo charcoal particles, the concentration of ethyl cellulose in ether is 20-30g / L, the concentration of bamboo charcoal fine powder in the dissolving solution is 10-15g / L, the ultrasonic frequency of ultrasonic treatment is 60-80kHz, the temperature is 5-10℃, and the drying temperature is 40-50℃. This step utilizes the solubility of ethyl cellulose in ether to form a low-concentration dispersion, and forms a surface coating on the bamboo charcoal fine powder. During filtration, an ethyl cellulose-ether liquid film is formed on the surface of the bamboo charcoal fine powder, and the ether is removed during drying, thereby ensuring that an ethyl cellulose liquid film is deposited on the surface of the bamboo charcoal fine powder.
[0009] a3, methyltrichlorosilane and ether are mixed to form a diluent, and then sprayed on the surface of the coated bamboo charcoal particles to form a liquid film, and the prefabricated modified bamboo charcoal particles are obtained by drying, standing and heating. The volume ratio of methyltrichlorosilane to ether is 1:3-5, the spraying speed is 3-5mL / min, the spraying time is 2-4s, the drying temperature is 40-45°C, and the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the nitrogen and water vapor are The volume ratio is 10-12:1, and the temperature of the heating and standing is 80-100°C; in this step, the methyltrichlorosilane is diluted by utilizing the compatibility of methyltrichlorosilane and ether, and then sprayed on the surface of the coated bamboo charcoal particles to form a liquid film, and the ether is removed during drying to form a methyltrichlorosilane surface film, which is hydrolyzed in situ with water vapor to form methyltrihydroxysilane, and the methyltrihydroxysilane is polycondensed during the heating and standing process to obtain a methyl-containing silicon oxygen polycondensation layer.
[0010] a4, treating the prefabricated modified bamboo charcoal particles with ultraviolet light for 2-3h, and then purging with nitrogen to obtain modified bamboo charcoal particles, the power of the ultraviolet light treatment is 200-300W, the nitrogen temperature of the nitrogen purging is 80-100°C, and the speed is 10-20mL / min; this step utilizes ultraviolet light treatment to degrade ethyl cellulose, and utilizes the light transmittance of the silicone condensation layer to ensure the complete removal of ethyl cellulose and also ensure that the surface of the bamboo charcoal fine powder is exposed.
[0011] The surface of the modified bamboo charcoal particles prepared by the method contains a silicon-oxygen condensation layer, which contains methyl groups, improves the surface unevenness, and has good stability in physical fixation. At the same time, the silicon-oxygen condensation layer contains active silicon hydroxyl groups, which show a certain electronegativity, which is the same as the surface of most bacteria. Therefore, the silicon-oxygen condensation layer can play a good antibacterial effect; the silicon-oxygen condensation layer has a silicon-oxygen mesoporous structure, which provides a negative ion release channel for the bamboo charcoal particles, and the silicon-oxygen mesoporous structure can play a water-blocking effect, ensuring internal stability and long-term effectiveness; the negative ions released by the bamboo charcoal particles are the same as the electrical properties of the silicon hydroxyl groups, and have a certain repulsiveness, ensuring that the negative ions are released outward without accumulation. Therefore, the modified bamboo charcoal particles not only have physical and chemical connection stability on the surface, but also use the negative ions of the bamboo charcoal particles and the silicon-oxygen electronegativity to form an antibacterial and sterilization effect.
[0012] Among them, the reinforcing filler adopts porous silicone filler, which uses its own porous structure to form structural gaps, ensures the penetration of polyethylene terephthalate, achieves the effect of physical clamping, and greatly improves the physical stability. The porous silicone filler has its own silicone stable structure and transparency, which not only improves the mechanical stability and wear resistance of the DTY low-elastic yarn, but also can form good color transferability, ensuring the color stability of the DTY low-elastic yarn.
[0013] The preparation method of the porous silicone filler comprises the following steps: b1, adding dodecyltrimethoxysilane, hexadecyltrimethoxysilane and butyltriethoxysilane to ether and stirring evenly to form a mixed solution, then adding ethyl cellulose and ultrasonically treating for 20-30 minutes to obtain a mixed dispersion, wherein the molar ratio of the dodecyltrimethoxysilane, hexadecyltrimethoxysilane and butyltriethoxysilane is 1:1-2:2-4, the concentration of the dodecyltrimethoxysilane in ether is 40-80g / L, the stirring speed is 300-500r / min, the concentration of the ethyl cellulose in ether is 70-100g / L, the temperature of the ultrasonic treatment is 5-10°C, and the ultrasonic frequency is 80-100kHz; this step utilizes that ethyl cellulose, dodecyltrimethoxysilane, hexadecyltrimethoxysilane and butyltriethoxysilane have good solubility in ether and can be homogeneously dispersed under ultrasonic action.
[0014] b2, spraying the mixed dispersion into a reactor, and obtaining hydrolyzed particles through deposition and purging, wherein the spraying speed is 5-10L / min, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1, and the temperature is 40-50°C; the deposition temperature is 100-110°C, and the purging adopts dry nitrogen at 80-90°C, and the purging speed is 5-10mL / min. In this step, the droplets are dispersed into the reactor by spraying, and composite particles are formed by evaporation in ether, and the atmosphere contains water vapor to ensure that dodecyltrimethoxysilane, hexadecyltrimethoxysilane and butyltriethoxysilane are hydrolyzed in situ, and the hydrolyzate after deposition treatment will form a condensation reaction to obtain silicon-oxygen composite particles containing long and short chains.
[0015] b3, placing the hydrolyzed particles in ethanol and ultrasonically treating them for 1-2 hours, filtering and washing them 1-3 times, spray drying to obtain porous silica fillers, wherein the concentration of the hydrolyzed particles in ethanol is 100-300 g / L, the temperature of the ultrasonic treatment is 30-40°C, the frequency is 70-90 kHz, ethanol is used for the washing, and the temperature of the spray drying is 100-120°C. The porous silica filler prepared by this method not only contains a porous structure formed by ethyl cellulose pores, but also has mesopores formed by polycondensation of silanol groups. At the same time, the porous structure of the porous silica filler contains active silanol groups, forming an antibacterial effect of an electronegative system, and also has a long branch-short branch fixed structure located outside the porous structure.
[0016] It can be seen from the above description that the present invention has the following advantages: 1. The present invention solves the problem of poor antibacterial stability of existing polyester low-elastic yarns, utilizes bamboo charcoal particles to form a negative ion release system, and cooperates with the surface of bamboo charcoal particles to form silicon oxygen mesoporous release channels and barrier properties, thereby ensuring the antibacterial and stability of polyester low-elastic yarns.
[0017] 2. The present invention utilizes porous silica filler as a reinforcing filler, which not only forms a physical permeability fixing effect, but also utilizes the transparency of silica materials to ensure the color transfer of the masterbatch.
[0018] 3. The present invention utilizes silicon-encapsulated bamboo charcoal particles and porous silicon fillers as dopants to enhance the mechanical properties of silicon materials. At the same time, the silicon hydroxyl groups brought by the silicon materials can be fixed with the hydrophilic groups in polyethylene terephthalate, thereby ensuring the stability of the polyester low-elastic yarn. DETAILED DESCRIPTION
[0019] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention. Example 1
[0020] A method for preparing negative ion antibacterial modified colored DTY low-elastic yarn comprises the following steps: Step 1, pre-crystallizing polyethylene terephthalate slices at high temperature, then drying, and ball milling to obtain pre-crystallized polyethylene terephthalate fine powder, wherein the high temperature pre-crystallization temperature is 170° C., the drying temperature is 180° C., and the time is 5 hours; the ball milling pressure is 0.4 MPa and the temperature is 5° C.; Step 2, adding modified anion fine powder, masterbatch and reinforcing filler to pre-crystallized polyethylene terephthalate fine powder and mixing them evenly, then adding them to a twin-screw extruder for melt extrusion to obtain a mixed melt, wherein the mass ratio of the mixed melt is: 180 parts of pre-crystallized polyethylene terephthalate fine powder, 8 parts of modified anion fine powder, 3 parts of masterbatch, and 5 parts of reinforcing filler; the modified anion fine powder adopts modified bamboo charcoal particles, the masterbatch adopts magenta masterbatch, and the reinforcing filler adopts porous silica filler; the temperature of the melt extrusion is 280°C and the pressure is 7MPa; Step 3, adding the mixed melt into the spinning box, and cooling it evenly into POY with annular blowing, and obtaining the negative ion antibacterial modified colored DTY low-elastic yarn through texturing treatment, wherein the spinning temperature is 285°C, the temperature of the annular blowing is 22°C, the wind speed is 0.5m / s, and the humidity is 65%; the texturing treatment is to sequentially spin the yarn through a pre-network nozzle, a yarn guide, a first roller, a false twister, a second roller, a final network, a third roller and a winding roller to obtain a polyester low-elastic yarn.
[0021] The modified bamboo charcoal particles are made of silicon-oxygen wrapped bamboo charcoal particles, and there are gaps between the bamboo charcoal particles and the silicon-oxygen wrapped layer. The preparation method of the silicon-oxygen wrapped bamboo charcoal particles includes the following steps: a1, wet grinding the bamboo charcoal particles for 2 hours, and obtaining bamboo charcoal fine powder after evaporation; the wet grinding uses ether as a solvent, and the mass ratio of bamboo charcoal particles to ether is 3:1, and the grinding pressure is 0.3MPa; the evaporation temperature is 40°C; a2, ethyl cellulose is placed in ether to form a dissolving solution, and the bamboo charcoal fine powder is placed in it, and after ultrasonic treatment for 1 hour, it is filtered and dried to obtain coated bamboo charcoal particles, the concentration of ethyl cellulose in ether is 20g / L, the concentration of bamboo charcoal fine powder in the dissolving solution is 10g / L, the ultrasonic frequency of the ultrasonic treatment is 60kHz, the temperature is 5°C, and the The drying temperature is 40°C; a3, methyltrichlorosilane and ether are mixed to form a diluent, and then sprayed on the surface of the coated bamboo charcoal particles to form a liquid film, and prefabricated modified bamboo charcoal particles are obtained by drying, standing and heating and standing, the volume ratio of methyltrichlorosilane to ether is 1:3, the spraying speed is 3mL / min, the spraying time is 2s, the drying temperature is 40°C, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10:1, and the heating and standing temperature is 80°C; a4, the prefabricated modified bamboo charcoal particles are treated with ultraviolet light for 2h, and then nitrogen purged to obtain modified bamboo charcoal particles, the power of the ultraviolet light treatment is 200W, the nitrogen temperature of the nitrogen purging is 80°C, and the speed is 10mL / min.
[0022] The reinforcing filler is a porous silicone filler, and the preparation method of the porous silicone filler comprises the following steps: b1, adding dodecyltrimethoxysilane, hexadecyltrimethoxysilane and butyltriethoxysilane to ether and stirring evenly to form a mixed solution, then adding ethyl cellulose and ultrasonically treating for 20 minutes to obtain a mixed dispersion, wherein the molar ratio of dodecyltrimethoxysilane, hexadecyltrimethoxysilane and butyltriethoxysilane is 1:1:2, the concentration of dodecyltrimethoxysilane in ether is 40g / L, the stirring speed is 300r / min, the concentration of ethyl cellulose in ether is 70g / L, the temperature of the ultrasonic treatment is 5°C, and the ultrasonic frequency is 8 0kHz; b2, spraying the mixed dispersion into a reactor, and obtaining hydrolyzed particles through deposition and purging, the spraying speed is 5L / min, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, and the temperature is 40°C; the deposition temperature is 100°C, the purging uses dry nitrogen at 80°C, and the purging speed is 5mL / min; b3, placing the hydrolyzed particles in ethanol for ultrasonic treatment for 1h, filtering and washing once, and spray drying to obtain porous silica filler, the concentration of the hydrolyzed particles in ethanol is 100g / L, the temperature of ultrasonic treatment is 30°C, the frequency is 70kHz, ethanol is used for washing, and the temperature of spray drying is 100°C. Example 2
[0023] A method for preparing negative ion antibacterial modified colored DTY low-elastic yarn comprises the following steps: Step 1, pre-crystallizing polyethylene terephthalate slices at high temperature, then drying, and obtaining pre-crystallized polyethylene terephthalate fine powder after ball milling, wherein the temperature of the high temperature pre-crystallization is 175° C., the temperature of the drying treatment is 185° C., and the time is 7 hours; the pressure of the ball milling treatment is 0.6 MPa and the temperature is 10° C.; Step 2, adding modified anion fine powder, masterbatch and reinforcing filler to pre-crystallized polyethylene terephthalate fine powder and mixing evenly, then adding to a twin-screw extruder for melt extrusion to obtain a mixed melt, wherein the mass ratio of the mixed melt is: 200 parts of pre-crystallized polyethylene terephthalate fine powder, 10 parts of modified anion fine powder, 5 parts of masterbatch, and 10 parts of reinforcing filler; the modified anion fine powder adopts modified bamboo charcoal particles, the masterbatch adopts cyan masterbatch, and the reinforcing filler adopts porous silica filler; the temperature of the melt extrusion is 290° C. and the pressure is 8 MPa; Step 3, adding the mixed melt into the spinning box, and cooling it evenly into POY with annular blowing, and obtaining the negative ion antibacterial modified colored DTY low-elastic yarn through texturing treatment, wherein the spinning temperature is 295°C, the temperature of the annular blowing is 25°C, the wind speed is 0.7m / s, and the humidity is 85%; the texturing treatment is to sequentially spin the yarn through a pre-network nozzle, a yarn guide, a first roller, a false twister, a second roller, a final network, a third roller and a winding roller to obtain a polyester low-elastic yarn.
[0024] The modified bamboo charcoal particles are made of silicon-oxygen wrapped bamboo charcoal particles, and there are gaps between the bamboo charcoal particles and the silicon-oxygen wrapped layer. The preparation method of the silicon-oxygen wrapped bamboo charcoal particles includes the following steps: a1, wet grinding the bamboo charcoal particles for 4 hours, and obtaining bamboo charcoal fine powder after evaporation; the wet grinding uses ether as a solvent, and the mass ratio of bamboo charcoal particles to ether is 5:1, and the grinding pressure is 0.5MPa; the evaporation temperature is 50°C; a2, ethyl cellulose is placed in ether to form a dissolving solution, and the bamboo charcoal fine powder is placed in it, and after ultrasonic treatment for 2 hours, it is filtered and dried to obtain coated bamboo charcoal particles, the concentration of ethyl cellulose in ether is 30g / L, the concentration of bamboo charcoal fine powder in the dissolving solution is 15g / L, the ultrasonic frequency of the ultrasonic treatment is 80kHz, the temperature is 10°C, and the The drying temperature is 50°C; a3, methyltrichlorosilane and ether are mixed to form a diluent, and then sprayed on the surface of the coated bamboo charcoal particles to form a liquid film, and prefabricated modified bamboo charcoal particles are obtained by drying, standing and heating and standing, the volume ratio of methyltrichlorosilane to ether is 1:5, the spraying speed is 5mL / min, the spraying time is 4s, the drying temperature is 45°C, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 12:1, and the heating and standing temperature is 100°C; a4, the prefabricated modified bamboo charcoal particles are treated with ultraviolet light for 3h, and then nitrogen purged to obtain modified bamboo charcoal particles, the power of the ultraviolet light treatment is 300W, the nitrogen temperature of the nitrogen purging is 100°C, and the speed is 20mL / min.
[0025] The reinforcing filler is a porous silica filler, and the preparation method of the porous silica filler comprises the following steps: b1, adding dodecyltrimethoxysilane, hexadecyltrimethoxysilane and butyltriethoxysilane to ether and stirring evenly to form a mixed solution, then adding ethyl cellulose and ultrasonically treating for 30 minutes to obtain a mixed dispersion, wherein the molar ratio of dodecyltrimethoxysilane, hexadecyltrimethoxysilane and butyltriethoxysilane is 1:2:4, the concentration of dodecyltrimethoxysilane in ether is 80g / L, the stirring speed is 500r / min, the concentration of ethyl cellulose in ether is 100g / L, the temperature of the ultrasonic treatment is 10°C, and the ultrasonic frequency is 10 0kHz; b2, spraying the mixed dispersion into a reactor, and obtaining hydrolyzed particles through deposition and purging, the spraying speed is 10L / min, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10:1, and the temperature is 50°C; the deposition temperature is 110°C, the purging uses dry nitrogen at 90°C, and the purging speed is 10mL / min; b3, placing the hydrolyzed particles in ethanol for ultrasonic treatment for 2h, filtering and washing 3 times, and spray drying to obtain porous silica filler, the concentration of the hydrolyzed particles in ethanol is 300g / L, the temperature of ultrasonic treatment is 40°C, the frequency is 90kHz, ethanol is used for washing, and the temperature of spray drying is 120°C. Example 3
[0026] A method for preparing negative ion antibacterial modified colored DTY low-elastic yarn comprises the following steps: Step 1, pre-crystallizing polyethylene terephthalate slices at high temperature, then drying, and obtaining pre-crystallized polyethylene terephthalate fine powder after ball milling, wherein the temperature of the high temperature pre-crystallization is 175° C., the temperature of the drying treatment is 185° C., and the time is 6 hours; the pressure of the ball milling treatment is 0.5 MPa and the temperature is 8° C.; Step 2, adding modified anion fine powder, masterbatch and reinforcing filler to pre-crystallized polyethylene terephthalate fine powder and mixing evenly, then adding to a twin-screw extruder for melt extrusion to obtain a mixed melt, wherein the mass ratio of the mixed melt is: 190 parts of pre-crystallized polyethylene terephthalate fine powder, 9 parts of modified anion fine powder, 4 parts of masterbatch, and 8 parts of reinforcing filler; the modified anion fine powder adopts modified bamboo charcoal particles, the masterbatch adopts yellow masterbatch, and the reinforcing filler adopts porous silica filler; the temperature of the melt extrusion is 285° C. and the pressure is 8 MPa; Step 3, adding the mixed melt into the spinning box, and cooling it evenly into POY with annular blowing, and obtaining the negative ion antibacterial modified colored DTY low-elastic yarn through texturing treatment, wherein the spinning temperature is 290°C, the temperature of the annular blowing is 24°C, the wind speed is 0.6m / s, and the humidity is 80%; the texturing treatment is to sequentially spin the yarn through a pre-network nozzle, a yarn guide, a first roller, a false twister, a second roller, a final network, a third roller, and a winding roller to obtain a polyester low-elastic yarn.
[0027] The modified bamboo charcoal particles are made of silicon-oxygen wrapped bamboo charcoal particles, and there are gaps between the bamboo charcoal particles and the silicon-oxygen wrapped layer. The preparation method of the silicon-oxygen wrapped bamboo charcoal particles includes the following steps: a1, wet grinding the bamboo charcoal particles for 3 hours, and obtaining bamboo charcoal fine powder after evaporation; the wet grinding uses ether as a solvent, and the mass ratio of bamboo charcoal particles to ether is 4:1, and the grinding pressure is 0.4MPa; the evaporation temperature is 45°C; a2, ethyl cellulose is placed in ether to form a dissolving solution, and the bamboo charcoal fine powder is placed in it, and after ultrasonic treatment for 2 hours, it is filtered and dried to obtain coated bamboo charcoal particles, the concentration of ethyl cellulose in ether is 25g / L, the concentration of bamboo charcoal fine powder in the dissolving solution is 13g / L, the ultrasonic frequency of the ultrasonic treatment is 70kHz, the temperature is 8°C, and the The drying temperature is 45°C; a3, methyltrichlorosilane and ether are mixed to form a diluent, and then sprayed on the surface of the coated bamboo charcoal particles to form a liquid film, and prefabricated modified bamboo charcoal particles are obtained by drying, standing and heating and standing, the volume ratio of methyltrichlorosilane to ether is 1:4, the spraying speed is 4mL / min, the spraying time is 3s, the drying temperature is 43°C, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 11:1, and the heating and standing temperature is 90°C; a4, the prefabricated modified bamboo charcoal particles are treated with ultraviolet light for 3h, and then nitrogen purged to obtain modified bamboo charcoal particles, the power of the ultraviolet light treatment is 250W, the nitrogen temperature of the nitrogen purging is 90°C, and the speed is 15mL / min.
[0028] The reinforcing filler is a porous silicone filler, and the preparation method of the porous silicone filler comprises the following steps: b1, adding dodecyltrimethoxysilane, hexadecyltrimethoxysilane and butyltriethoxysilane to ether and stirring evenly to form a mixed solution, then adding ethyl cellulose and ultrasonically treating for 25 minutes to obtain a mixed dispersion, wherein the molar ratio of dodecyltrimethoxysilane, hexadecyltrimethoxysilane and butyltriethoxysilane is 1:2:3, the concentration of dodecyltrimethoxysilane in ether is 60g / L, the stirring speed is 400r / min, the concentration of ethyl cellulose in ether is 80g / L, the temperature of the ultrasonic treatment is 8°C, and the ultrasonic frequency is 9 0kHz; b2, spraying the mixed dispersion into a reactor, and obtaining hydrolyzed particles through deposition and purging, the spraying speed is 8L / min, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 9:1, and the temperature is 45°C; the deposition temperature is 105°C, the purging adopts dry nitrogen at 85°C, and the purging speed is 8mL / min; b3, placing the hydrolyzed particles in ethanol for ultrasonic treatment for 2h, filtering and washing twice, and spray drying to obtain porous silica filler, the concentration of the hydrolyzed particles in ethanol is 200g / L, the temperature of ultrasonic treatment is 35°C, the frequency is 80kHz, ethanol is used for washing, and the temperature of spray drying is 110°C. Example 4
[0029] A method for preparing negative ion antibacterial modified colored DTY low-elastic yarn comprises the following steps: Step 1, pre-crystallizing polyethylene terephthalate slices at high temperature, then drying, and obtaining pre-crystallized polyethylene terephthalate fine powder after ball milling, wherein the temperature of the high temperature pre-crystallization is 175° C., the temperature of the drying treatment is 185° C., and the time is 6 hours; the pressure of the ball milling treatment is 0.5 MPa and the temperature is 8° C.; Step 2, adding modified anion fine powder, masterbatch and reinforcing filler to pre-crystallized polyethylene terephthalate fine powder and mixing them evenly, then adding them to a twin-screw extruder for melt extrusion to obtain a mixed melt, wherein the mass ratio of the mixed melt is: 190 parts of pre-crystallized polyethylene terephthalate fine powder, 9 parts of modified anion fine powder, 4 parts of masterbatch, and 8 parts of reinforcing filler; the modified anion fine powder adopts modified bamboo charcoal particles, the masterbatch adopts yellow masterbatch, and the reinforcing filler adopts silica particles; the temperature of the melt extrusion is 285° C. and the pressure is 8 MPa; Step 3, adding the mixed melt into the spinning box, and cooling it evenly into POY with annular blowing, and obtaining the negative ion antibacterial modified colored DTY low-elastic yarn through texturing treatment, wherein the spinning temperature is 290°C, the temperature of the annular blowing is 24°C, the wind speed is 0.6m / s, and the humidity is 80%; the texturing treatment is to sequentially spin the yarn through a pre-network nozzle, a yarn guide, a first roller, a false twister, a second roller, a final network, a third roller, and a winding roller to obtain a polyester low-elastic yarn.
[0030] The modified bamboo charcoal particles are made of silicon-oxygen wrapped bamboo charcoal particles, and there are gaps between the bamboo charcoal particles and the silicon-oxygen wrapped layer. The preparation method of the silicon-oxygen wrapped bamboo charcoal particles includes the following steps: a1, wet grinding the bamboo charcoal particles for 3 hours, and obtaining bamboo charcoal fine powder after evaporation; the wet grinding uses ether as a solvent, and the mass ratio of bamboo charcoal particles to ether is 4:1, and the grinding pressure is 0.4MPa; the evaporation temperature is 45°C; a2, ethyl cellulose is placed in ether to form a dissolving solution, and the bamboo charcoal fine powder is placed in it, and after ultrasonic treatment for 2 hours, it is filtered and dried to obtain coated bamboo charcoal particles, the concentration of ethyl cellulose in ether is 25g / L, the concentration of bamboo charcoal fine powder in the dissolving solution is 13g / L, the ultrasonic frequency of the ultrasonic treatment is 70kHz, the temperature is 8°C, and the The drying temperature is 45°C; a3, methyltrichlorosilane and ether are mixed to form a diluent, and then sprayed on the surface of the coated bamboo charcoal particles to form a liquid film, and prefabricated modified bamboo charcoal particles are obtained by drying, standing and heating and standing, the volume ratio of methyltrichlorosilane to ether is 1:4, the spraying speed is 4mL / min, the spraying time is 3s, the drying temperature is 43°C, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 11:1, and the heating and standing temperature is 90°C; a4, the prefabricated modified bamboo charcoal particles are treated with ultraviolet light for 3h, and then nitrogen purged to obtain modified bamboo charcoal particles, the power of the ultraviolet light treatment is 250W, the nitrogen temperature of the nitrogen purging is 90°C, and the speed is 15mL / min. Example 5
[0031] A method for preparing negative ion antibacterial modified colored DTY low-elastic yarn comprises the following steps: Step 1, pre-crystallizing polyethylene terephthalate slices at high temperature, then drying, and obtaining pre-crystallized polyethylene terephthalate fine powder after ball milling, wherein the temperature of the high temperature pre-crystallization is 175° C., the temperature of the drying treatment is 185° C., and the time is 6 hours; the pressure of the ball milling treatment is 0.5 MPa and the temperature is 8° C.; Step 2, adding the anion fine powder, the masterbatch and the reinforcing filler to the pre-crystallized polyethylene terephthalate fine powder and mixing them evenly, and then adding them to a twin-screw extruder for melt extrusion to obtain a mixed melt, wherein the mass ratio of the mixed melt is: 190 parts of pre-crystallized polyethylene terephthalate fine powder, 9 parts of the anion fine powder, 4 parts of the masterbatch, and 8 parts of the reinforcing filler; the anion fine powder is bamboo charcoal particles, the masterbatch is yellow masterbatch, and the reinforcing filler is silica particles; the temperature of the melt extrusion is 285° C. and the pressure is 8 MPa; Step 3, adding the mixed melt into the spinning box, and cooling it evenly into POY with annular blowing, and obtaining the negative ion antibacterial modified colored DTY low-elastic yarn through texturing treatment, wherein the spinning temperature is 290°C, the temperature of the annular blowing is 24°C, the wind speed is 0.6m / s, and the humidity is 80%; the texturing treatment is to sequentially spin the yarn through a pre-network nozzle, a yarn guide, a first roller, a false twister, a second roller, a final network, a third roller, and a winding roller to obtain a polyester low-elastic yarn.
[0032] Comparative Example The comparative example uses commercially available antibacterial DTY low-elastic yarn, which is selected from the antibacterial polyester low-elastic yarn of a new material company in Zhejiang.
[0033] Performance Testing The products of Examples 1-5 and the comparative example were used as test samples to perform performance tests, and the results are as follows: 1. Weave DTY low-elastic yarn into 10cm*10cm fabric and test the antibacterial properties of the fabric Table 1 Antibacterial test
[0034] The above fabrics were washed 50 times and then tested for antibacterial stability. Table 2 Antimicrobial stability test
[0035] It can be seen from Tables 1 and 2 that the colored DTY low-elastic yarn of the present technical solution has good antibacterial properties, and the antibacterial stability comes from the negative ion system. Compared with the commercially available polyester low-elastic yarn in the comparative example, the present technical solution still maintains good antibacterial effect after multiple washings. The main reason is that the silicone shell protects the bamboo charcoal particles, preventing the infiltration of distilled water without affecting the release of negative ions.
[0036] 2. Mechanical properties test of DTY low elastic yarn Table 3 Mechanical properties test
[0037] It can be seen from Table 3 that the DTY low-elastic yarn prepared by the present technical solution has good mechanical properties, which are close to the performance of commercially available antibacterial polyester low-elastic yarn and meet the current market demand.
[0038] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.
Claims
1. A method for preparing negative ion antibacterial modified colored DTY low-elastic yarn, characterized in that: The steps include: Step 1, pre-crystallizing polyethylene terephthalate slices at high temperature, then drying them, and obtaining pre-crystallized polyethylene terephthalate fine powder after ball milling; Step 2, adding modified anion fine powder, masterbatch and reinforcing filler to pre-crystallized polyethylene terephthalate fine powder and mixing them evenly, and then adding them to a twin-screw extruder for melt extrusion to obtain a mixed melt; the modified anion fine powder adopts modified bamboo charcoal particles; and the modified bamboo charcoal particles adopt silicon-oxygen wrapped bamboo charcoal particles, and there is a gap between the bamboo charcoal particles and the silicon-oxygen wrapped layer; Step 3, adding the mixed melt into a spinning box, and cooling it uniformly into POY by ring blowing, and obtaining anion antibacterial modified colored DTY low-elastic yarn by elastic treatment; The preparation method of silicon-oxygen coated bamboo charcoal particles comprises the following steps: a1, wet-grinding bamboo charcoal particles for 2-4 hours, and obtaining bamboo charcoal fine powder after evaporation; a2, placing ethyl cellulose in ether to form a dissolving solution, and placing bamboo charcoal fine powder in the solution, ultrasonically treating the solution for 1-2 hours, and filtering and drying the solution to obtain coated bamboo charcoal particles; a3, mixing methyltrichlorosilane with ether to form a diluent, and then spraying the solution on the surface of the coated bamboo charcoal particles to form a liquid film, and obtaining prefabricated modified bamboo charcoal particles after drying, standing and heating and standing; a4, treating the prefabricated modified bamboo charcoal particles with ultraviolet light for 2-3 hours, and then purging with nitrogen to obtain modified bamboo charcoal particles.
2. The method for preparing the negative ion antibacterial modified colored DTY low-elastic yarn according to claim 1, characterized in that: The temperature of the high temperature pre-crystallization in step 1 is 170-175° C., the temperature of the drying treatment is 180-185° C., and the time is 5-7 hours.
3. The method for preparing the negative ion antibacterial modified colored DTY low-elastic yarn according to claim 1, characterized in that: The ball milling process in step 1 is performed at a pressure of 0.4-0.6 MPa and a temperature of 5-10°C.
4. The method for preparing the negative ion antibacterial modified colored DTY low-elastic yarn according to claim 1, characterized in that: The mass ratio of the mixed melt in step 2 is: 180-200 parts of pre-crystallized polyethylene terephthalate fine powder, 8-10 parts of modified anion fine powder, 3-5 parts of masterbatch, and 5-10 parts of reinforcing filler.
5. The method for preparing the negative ion antibacterial modified colored DTY low-elastic yarn according to claim 4, characterized in that: The masterbatch is one or more of magenta masterbatch, cyan masterbatch and yellow masterbatch.
6. The method for preparing the negative ion antibacterial modified colored DTY low-elastic yarn according to claim 4, characterized in that: The reinforcing filler is a porous silica filler.
7. The method for preparing the negative ion antibacterial modified colored DTY low-elastic yarn according to claim 1, characterized in that: The temperature of the melt extrusion in step 2 is 280-290° C. and the pressure is 7-8 MPa.
8. The method for preparing the negative ion antibacterial modified colored DTY low-elastic yarn according to claim 1, characterized in that: The spinning temperature in step 3 is 285-295° C., the temperature of the annular air is 22-25° C., the wind speed is 0.5-0.7 m / s, and the humidity is 65-85%.
9. The method for preparing the negative ion antibacterial modified colored DTY low-elastic yarn according to claim 1, characterized in that: The texturing treatment in step 3 is to sequentially spin the yarn through a pre-netting nozzle, a yarn guide, a first roller, a false twister, a second roller, a final netting, a third roller and a winding roller, thereby obtaining polyester low-stretch yarn.
10. The method for preparing the negative ion antibacterial modified colored DTY low-elastic yarn according to claim 1, characterized in that: In a1, the wet grinding uses ether as solvent, and the mass ratio of bamboo charcoal particles to ether is 3-5:1, the grinding pressure is 0.3-0.5 MPa; the evaporation temperature is 40-50°C; In a2, the concentration of ethyl cellulose in ether is 20-30 g / L, the concentration of bamboo charcoal powder in the dissolving solution is 10-15 g / L, the ultrasonic frequency of the ultrasonic treatment is 60-80 kHz, the temperature is 5-10° C., and the drying temperature is 40-50° C.; In a3, the volume ratio of methyltrichlorosilane to diethyl ether is 1:3-5, the spraying speed is 3-5 mL / min, the spraying time is 2-4 s, the drying temperature is 40-45 ° C, the static atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10-12:1, and the temperature of the heating and static is 80-100 ° C; In a4, the power of the ultraviolet light treatment is 200-300W, the nitrogen temperature of the nitrogen purge is 80-100°C, and the speed is 10-20mL / min.
Citation Information
Patent Citations
Photocatalytic aerogel contained bamboo charcoal-based adsorption and decomposition agent as well as its preparation method
CN102430386A
Manufacturing method of special-shaped hollow warmth keeping polyester drawn textured yarn
CN105908269A
Preparation method of composite sterilization material for air purification
CN111466373A
Preparation method of efficient photocatalyst with fly ash as carrier
CN115254086A
Preparation method of wear-resistant filler
CN117418417A
